Pyridoxal kinase and poly(ADP-ribose) affect the immune microenvironment of locally advanced cancers. (1st January 2021) - Joseph, Adrien; Pan, Juncheng; Michels, Judith; Kroemer, Guido; Castedo, Maria
ABSTRACT: Malignant cells adapt to the hostile tumor microenvironment by escaping from, or actively suppressing, anticancer immune responses. In the past, we reported that reduced synthesis of active vitamin B6 (due to downregulation of pyridoxal kinase) or overactivation of poly(ADP-ribose) polymerase confers resistance to chemotherapy with cisplatin. Recently, we found that these prognostically adverse alterations in oncometabolism also correlate with the rarefaction of immune effectors in the tumor bed.